Facilitating low-carbon investments: Lessons from natural gas - Anne Neumann; Karsten Neuhoff (Deutsches Institut für Wirtschaftsforschung (DIW), 2011)
Decarbonisation of energy and transport infrastructure requires significant private sector investments. The natural gas industry has demonstrated such large scale private sector infrastructure investment over the last decades, typically using long-term contractual arrangements. Are therefore institutional frameworks necessary that facilitate long-term contracting or provide regulation reassuring about future resource streams associated with low-carbon infrastructure - or do factors idiosyncratic to natural gas explain the prevalence of long-term contracts in natural gas infrastructure investment? We identify four reasons for the use of long-term contracting arrangements. The transformation of the natural gas industry and regulatory structure has gradually reduced the rational for three of these reasons, suggesting that remaining rational, securing of revenue streams to finance investments has become the main motivation for the use of long-term contracts. This rational is not idiosyncratic to the natural gas industry, and thus suggests that long-term contracting can also play a significant role in facilitating low-carbon infrastructure investment. We furthermore discuss the role of institutional frameworks necessary for long-term contracting, and identify the significant role governments have been playing in sharing the counterparty risk inherent in long-term contracts.
Keywords: L78; O13; Q58; 330; Investment; low-carbon economy; natural gas